Simultaneous upper and lower body perfusion using hypothermia during thoracoabdominal aortic surgery - Yuya Kise; Yukio Kuniyoshi; Mizuki Ando; Keita Miyaishi; Shotaro Higa; Tatuya Maeda; Moriyasu Nakaema; Hitoshi Inafuku; Kojiro Furukawa (Journal of Cardiothoracic Surgery, 2023)
Abstract Background In open thoracoabdominal aortic aneurysm (TAAA) repair, we have been performing vascular reconstruction under moderate to deep hypothermia and assisted circulation using simultaneous upper and lower body perfusion. This method is effective for protecting the spinal cord and the brain, heart, and abdominal organs and for avoiding lung damage. Methods TAAA repair was performed under hypothermia at 20–28 °C in 18 cases (Crawford type I in 0 cases, type II in 5, type III in 3, type IV in 4, and Safi V in 6) between October 2014 and January 2023. Cardiopulmonary bypass was conducted by combined upper and lower body perfusion, with perfusion both via the femoral artery and either transapically or via the descending aorta or the left brachial artery. Results The ischemic time for the artery of Adamkiewicz and the main segmental arteries was 40–124 min (75 ± 33 min). No spinal cord ischemic injury or brain or heart complications occurred. One patient with postoperative right renal artery occlusion and one with an infected aneurysm required tracheostomy, but the intubation time for the other 16 was 32 ± 33 h. The duration of postoperative intensive care unit stay was 6.5 ± 6.2 days, the length of hospital stay was 29 ± 15 days, and no in-hospital deaths occurred. Conclusions Simultaneous upper and lower body perfusion under moderate to deep hypothermia during thoracoabdominal aortic surgery may avoid not only spinal cord injury, but also cardiac and brain complications.